EFFECT OF DEFAULT RISK, ACCOUNTING CONSERVATISM, PROFIT PERSISTENCE AND AUDIT QUALITY ON EARNINGS RESPONSE COEFFICIENT (ERC) IN NON-FINANCIAL COMPANIES REGISTERED ON THE INDONESIAN STOCK EXCHANGE (IDX) IN 2019-2021 - Muammar Khaddafi; Nasriani; Yunina; Mursidah; Damsar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to examine the effect of default risk, accounting conservatism, earnings persistence and audit quality on earnings response coefficient (ERC). The population in this study are non-financial companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021 with a total of 673 companies. Sampling in this study used purposive sampling and obtained as many as 118 companies with 354 observational data. This research is a quantitative research with secondary data sources including the company's annual financial reports obtained through the websitewww.idx.co.idand stock prices obtained through the sitehttp://finance.yahoo.com. Data collection techniques in this study are the method of documentation and literature study.Data analysis in this study used panel data regression using EViews 12 software. The results showed that default risk had no significant effect on earnings response coefficient (ERC), accounting conservatism and earnings persistence had no significant positive effect on earnings response coefficient (ERC). And audit quality has a negative and significant effect on earnings response coefficient (ERC).